Cozy Heterotopias in JRPGs: A Foucauldian Perspective on the Spatiality of Coziness in Japanese Role-Playing Games - Simond, Stefan H.; Klös, Tobias (Replay. The Polish Journal of Game Studies, 2024)
This article applies the concept of heterotopia as developed by Michel Foucault to cozy aesthetics in JRPGs. After introducing the concept of heterotopia and its six key principles, the term JRPG is briefly reflected upon. We then analyze key aspects of the games Ni no Kuni: Wrath of the White Witch and Final Fantasy VII Remake regarding the significance of heterotopias for their sense of coziness. We conclude that Foucault’s concept of heterotopia helps in understanding the way in which coziness, on the one hand, offers a respite from the crises of life while, on the other hand, enabling an engagement with said crises in a safe environment.